Pengaruh Formulasi Tepung Komposit (Tepung Terigu, Tepung Tempe Dan Tepung Jerami Nangka (Artocarpus heterophyllus)) Terhadap Kadar Protein, Serat Kasar Serta Daya Terima Cookies Sebagai Makanan Selingan Anak Obesitas - Christina Mumpuni Erawati; Nany Suryani; Zainun Nasriyah (Jurnal Kesehatan Indonesia, 2018)
Snacks or food interludes specially for child obesity is given between his or her staple food. The purpose of it is giving a good nutrition according to child age. Snack in this research is a cookies with the addition of tempe and jackfruit straw.flour. The purpose of this research is to know the influence of composite flour (wheat flour, tempe flour, and jackfruit straw flour) to the protein, fiber and acceptance of cookies. The method using experimental with randomized complete design (RCD). It consist of 4 treatments and 3 replications which is the formulation wheat flour, tempe flour, and jackfruit straw flour P1 (100%:0%:0%), P2 (70%:25%:5%), P3 (70%:20%:10%), and P4 (70%:15%:15%). Data analysis of protein and fiber content using one way anova .while for acceptance test using friedman analysis. The result of this research shows that there is an influence between composite flour formulation wheat flour, tempe flour and jackfruit straw flour with the highest value is P2 (27,31%) obtain by statistic result (p=0,000) and the fiber with the highest value is P4 (18,30%) and the statistic result is p=0,000. The acceptance analysis consist of color, aroma, tekstur and taste analysis. The higher score of color is achieved by P3, aroma is achieved by P3, texture is achieved by P1, taste is achieved by P3. Cookies with the composite flour formulation (wheat flour, tempe flour,and jackfruit flour) can be used as an obese child’s snacks and are advised to consume 1-2 servings daily for 4-12 years old to meet fiber and protein requirements based on 20% of AKG.